Evaluation of IoT Regulatory Readiness in Indonesia and Policy Recommendations to Support Safe and Effective Implementation - Robie, Rizqon; Munadi, Rendy; Jumhur, Helni Mutiarsih (International Journal of Artificial Intelligence Research, 2025)
The rapid development of Internet of Things (IoT) technology in Indonesia presents significant opportunities as well as regulatory challenges. Although IoT adoption continues to increase across various sectors, national policies remain fragmented and lack an integrated framework to support safe and effective implementation. This study assesses Indonesia's readiness for IoT regulation and formulates policy recommendations using a mixed-methods approach. The dataset used in this study comprises both secondary and primary data. Secondary data includes Indonesia's Cybersecurity data, Digital Infrastructure Status, IoT Regulations and Laws, Bappenas Studies, Data from Bappenas, and several policies in other countries, such as America, China, Japan, Korea, and Europe. Meanwhile, primary data was collected through questionnaires distributed to several elements, including 61.5% respondents from IoT users, 19.3% respondents from IoT business actors/IoT Startups, 15.8% academics, and 3.7% Government as regulators. The results of this data were then processed to determine government policy readiness by implementing DDPG, where the state space consists of 6 dimensions of leading regulatory readiness indicators (infrastructure, security, data protection, interoperability, institutional maturity, and economy). The action space is a 6-dimensional vector with continuous values in the range of [-1, 1], representing policy interventions in each dimension. The implementation applies reward functions, actor networks, and critic networks. Training data was applied for several episodes at 400 and 1000 episodes. The comparison results show that IoT regulations and policies in Indonesia should be designed with an adaptive approach based on Reinforcement learning, where the balance between data security, technology readiness, and market penetration can be dynamically adjusted to national and global conditions